Metal Complexes of Pyridine-3-Carboxyaldehde Thiosemicarbazone - Singh, Charanjit; Parwana, H.K.; Singh, Gajendra; Jolly, R.S. (Asian Journal of Chemistry, 2010)
Complexes of copper(II), cobalt(II), nickel(II), manganese(II), iron(lI) and iron(III), zinc(II) and silver(l) with pyidine-3-carboxaldehyde thiosernicarbawne (HNAT) are reported. Analytical, spectral, magnetic and conductance studies indicate that HNAT acts as a bidentate ligand in all its complexes coordinating through the nitrogen of the pyridine ring and sulphur atom. Polymeric six-coor-dinated ligand bridged structures have been proposed for all the complexes except [Co(HNAT)CI2], which has a polymeric four-coordinated structure.